Advances in insect physiology. - Berridge, Michael J.; Treherne, J. E.; Wigglesworth, Vincent B. (Vincent Brian), Sir, 1899-1994 (Advances in insect physiology ;, 1982)
ADVANCES IN INSECT PHYSIOLOGY VOL16 APL.